Empowering Dapur Ayuna Women's Group by implementing Good Manufacturing Practice (GMP) and Standard Sanitation Operational Procedure (SSOP) in Central Banjar, Buduk Village, Mengwi District, Badung Regency, Bali - Semariyani, A.A.Made; Ni Made Ayu Suardani Singapurwa; Luh Suariani (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2022)
In Bali, there are a variety of processed traditional foods that are still very popular with locals and even domestic and foreign tourists. In empowering rural communities, namely by increasing knowledge, attitudes, skills, behaviors, programs, or activities, assistance is needed following the needs of the community, in developing micro, small and medium enterprises. This PKM (community service) activity is carried out in support of the Strategic Plan's priorities, namely strengthening the quality and relevance of higher education, which will be carried out at the Dapur Ayuna Women's Group in Banjar Tengah, Buduk Village, Mengwi District, Badung Regency, Bali. This group is a productive group that has activities to process traditional processed food from meat and poultry. Traditional Processed Food Products have been produced and marketed by partners, but they have not been intensive, and partners want to increase their quantity and quality. Partners do not know the field of processing and entrepreneurship, so they experience obstacles in the management of production and marketing. The group asked to be given training and assistance on processed food products. Traditional processed food products are one of the foods that must be preserved and maintained in each region to maintain local wisdom. The Ayuna Kitchen Women's Group can produce a good implementation of good food processing methods (GMP) and Standard Sanitation Operational Procedure (SSOP) to produce products with quality.